2019
DOI: 10.1186/s12911-019-0814-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to help researchers evaluate biases in clinical trials: a prospective, randomized user study

Abstract: Objective Assessing risks of bias in randomized controlled trials (RCTs) is an important but laborious task when conducting systematic reviews. RobotReviewer (RR), an open-source machine learning (ML) system, semi-automates bias assessments. We conducted a user study of RobotReviewer, evaluating time saved and usability of the tool. Materials and methods Systematic reviewers applied the Cochrane Risk of Bias tool to four randomly selected RCT articles. Reviewers judged:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
0
31
0
2
Order By: Relevance
“…Recently, machine learning (ML) algorithms have used computational methods to “learn” information directly from data, and their performance has been shown to improve proportionally with the number of high-quality samples [ 8 ]. ML algorithms have been applied in different aspects of medicine [ 9 , 10 ], including earlier disease detection [ 11 , 12 ], improve diagnosis accuracy [ 13 – 16 ], identification of new physiological observations or patterns [ 17 ], development of personalized diagnostics and/or therapeutic approaches [ 18 , 19 ], research purposes [ 20 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning (ML) algorithms have used computational methods to “learn” information directly from data, and their performance has been shown to improve proportionally with the number of high-quality samples [ 8 ]. ML algorithms have been applied in different aspects of medicine [ 9 , 10 ], including earlier disease detection [ 11 , 12 ], improve diagnosis accuracy [ 13 – 16 ], identification of new physiological observations or patterns [ 17 ], development of personalized diagnostics and/or therapeutic approaches [ 18 , 19 ], research purposes [ 20 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study found that using RobotReviewer as a semi‐autonomous tool was nonetheless quicker on average than no automation by 69 seconds (for all studies analyzed). This 2019 study, outlined in BMC Medical Informatics and Decision Making , was performed with a small sample size and used a sample of reviewers not typical of a team of systematic reviewers (5 of the 41 volunteers had no experience with systematic reviews and nine had no experience with the risk of bias tool).…”
Section: Discussionmentioning
confidence: 91%
“…For example, reviewers might judge the tool’s accuracy as sufficient or helpful for its supportive use when facing a high number of studies for risk of bias assessment or facing studies that are reported in a different structure than in scientific journals such as grey literature publications. Furthermore, a recent study indicates that using RobotReviewer might be less time consuming than manual assessment by human reviewers (Soboczenski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, reviewers might judge the tool's accuracy as sufficient or helpful for its supportive use when facing a high number of studies for risk of bias assessment or facing studies that are reported in a different structure than in scientific journals such as grey literature publications. Furthermore, a recent study indicates that using RobotReviewer might be less time consuming than manual assessment by human reviewers (Soboczenski et al, 2019). Third, although the tool has not been developed to replace assessment by human reviewers (Marshall et al, 2016), research shows that RobotReviewer's reliability is comparable to that between two independent human reviewers (Hartling et al, 2013).…”
Section: Discussionmentioning
confidence: 99%